Patient Characteristics Associated with Non-Adherence to Anti Tuberculosis Treatment in Sri Lanka (SAARC Journal of Tuberculosis, Lung Diseases and HIV/AIDS, 2013)
Introduction: Sri Lanka had achieved a significant improvement in the tuberculosis control including a reduction of the default rate since introduction of the DOTS strategy to the National TB control Programme  in 1997. Patients’ adherence to anti TB treatment may be measured using either process oriented or outcome oriented definitions. Default rate is an outcome oriented definition that may be used as an indicator of poor patient adherence to anti TB treatment. One of the main obstacles in achieving the best  tuberculosis (TB) control is that patients do not complete full course of anti TB treatment. A prospective cohort study was carried out with the objective to identify patient characteristics that associate with defaulting anti tuberculosis treatment. Methodology: This was a prospective cohort study of new smear positive pulmonary tuberculosis patients registered for treatment between 1.6.2008 and 31.8.2008 in seven districts in Sri Lanka. Data on the patient characteristics and the plan of management were collected at the beginning of the treatment using a pre tested structured questionnaire. During the follow up and at the end of the treatment, results of sputum microscopy and the treatment outcome were recorded. The patients who interrupted treatment for 2 months or more (defaulters) during the course of treatment were again investigated in the field. In the statistical analysis, patient characteristics of the defaulters were compared with the characteristics of patients who were cured. Results: There were 22 defaulters giving a default rate of 4.59%. Being a male, poor educational background, having a casual job, regular smoking, and regular alcohol use were significantly associated with defaulting treatment (p < 0.05). Sinhalese had lower default rate than other ethnic groups. At the field investigation, 43% of the defaulters were found not living in the addresses given to the treatment providers. Field investigators have further reported that financial reasons, substance abuse, feeling well, and lack of family support also as causes of defaulting treatment. Conclusion: Identification of risk factors by careful patient interview, early home visit, and monitoring of patient behaviour early in the course of treatment will help to predict whether adherence is likely to be a  problem. So that, the treatment provider will be able to arrange a flexible and patient centered approach to ensure maximum adherence. SAARC Journal of Tuberculosis, Lung Diseases & HIV/AIDS; 2012; IX(2) 19-25 DOI: http://dx.doi.org/10.3126/saarctb.v9i2.7974